Awareness of Oral Cancer Among Professionals Practcing General Medicine and General Dentistry in Lahore - Saba Hanif, Armaghan Israr Mirza, Saadia Firdous, Nabeela Riaz, Samreen Younas, Zubair Ahmad, Zara Shakeel (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To inquire the oral cancer awareness among general medical and general dental professionalsand their knowledge of early detection and prevention of oral squamous cell carcinoma. Study design: cross sectional study Place and duration of study: Oral and maxillofacial surgery Department King Edward Medical University from 5th November 2019 to 5th February 2020. Methodology: A questionnaire was given to dental and medical practitioners and their responses were included in the results. This study was done in three months’ period from 5th November 2019 to 5th February 2020 after ethical approval from institutional review board. Results:The questions were given back by 57 general medical practitioners and by 40 general dental practitioners, producing return rates of 38% GMPs and 26.66% GDPs respectively. The questions were answered by 93 GMPs and by 110 GDPs producing rates of 62% GMPs and 73.33% GDPs respectively. Conclusion: Patients suffering from oral pathologies often go to their general medical practitioner and dental practitioners. The number of patientsof squamous cell carcinoma of oral cavity are rising in the Pakistan, hence general medical and general dental practitioners need to play significant role. This study talks mainly about the on the need for improvement in awareness about oral squamous cell carcinoma. Keywords: oral cancer, awareness, risk factors